The Effect of the Application of Outbound Games Learning Methods on the Problem-Solving Ability of Children Aged 5-6 Years Aisyiyah Bustanul Athfal Bulurokeng Kindergarten: A Quasi-Experimental Study - Alya, Namira; Syamsuardi, Syamsuardi; Bahri, Aliem; Martuty, Arie; Intisari , Intisari (JURNAL PENDIDIKAN USIA DINI, 2025)
This research is based on the problem of low problem-solving skills in early childhood, where children find it difficult to think, understand, and remember and are not able to solve their own problems. According to Weikart, exploration and problem solving are active ways for children to learn, which are considered important to help children become independent, make decisions, and be confident in facing new situations with problem solving. So this study aims to analyze the effect of implementing the outbound games learning method on the problem-solving skills of children aged 5-6 years. This study uses a quantitative approach with a quasi-experimental method with a one-group pre-test post-test design. The research subjects consisted of 15 children at Bustanul Athfan Bulurokeng Kindergarten Group B who were selected from the research population using a purposive sampling technique. Data were collected through observation guidelines that measure three main aspects: recognizing problems, finding solutions, and evaluating results. The results showed a significant increase that can be seen from children's abilities in identifying problems, thinking critically, logically, and independently in solving problems after the implementation of outbound games. There was a difference in the average pre-test score of 28.73, increasing to 58.13 in the post-test with a p-value of 0.001 (p < 0.05). The implementation of outbound games has proven effective as an experience-based learning method to improve the problem-solving skills of early childhood, so it can be a relevant alternative for educators.